2023
DOI: 10.18421/tem121-65
|View full text |Cite
|
Sign up to set email alerts
|

User Evaluation on a Mobile Augmented Reality Game-based Application as a Learning Tool for Biology

Abstract: It is challenging to comprehend abstract information on a scientific topic. In essence, AR could display abstract scientific information excitingly and graphically, improving the students' learning interests and performance. Their critical engagement could be enhanced further through AR's visualisation capability, achieved via active learning in an AR-game environment. Hence, this paper proposed and described a reflection on a mobile AR game, ARCell, involving cell biology. This game is designed to help studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Source: (Hong et al, 2018) From the 29 selected articles, a diverse array of research designs was identified. Among them, 11 studies adopted quantitative non-randomized research designs (Al-Muqbil, 2022; Damopolii et al, 2022;Gnidovec et al, 2020;Gregorcic & Torkar, 2022;Lam et al, 2023;Nurhayati et al, 2022;Petrov & Atanasova, 2020;Sivri & Eroglu, 2022;Stojšić, Ostojić, & Stanisavljević, 2022;Weng et al, 2020a;Yang & Tsai, 2021). An equal number of studies, 11 in total, utilized mixed-method research designs (Celik et al, 2020;Delgado-Rodríguez, Carrascal Domínguez, & Garcia-Fandino, 2023;Erbas & Demirer, 2019;Fuchsova & Korenova, 2019;Kozcu Cakir et al, 2020;Lo et al, 2021;Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021;Yapici & Karakoyun, 2021;Yildirim, 2020;Ziden et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Source: (Hong et al, 2018) From the 29 selected articles, a diverse array of research designs was identified. Among them, 11 studies adopted quantitative non-randomized research designs (Al-Muqbil, 2022; Damopolii et al, 2022;Gnidovec et al, 2020;Gregorcic & Torkar, 2022;Lam et al, 2023;Nurhayati et al, 2022;Petrov & Atanasova, 2020;Sivri & Eroglu, 2022;Stojšić, Ostojić, & Stanisavljević, 2022;Weng et al, 2020a;Yang & Tsai, 2021). An equal number of studies, 11 in total, utilized mixed-method research designs (Celik et al, 2020;Delgado-Rodríguez, Carrascal Domínguez, & Garcia-Fandino, 2023;Erbas & Demirer, 2019;Fuchsova & Korenova, 2019;Kozcu Cakir et al, 2020;Lo et al, 2021;Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021;Yapici & Karakoyun, 2021;Yildirim, 2020;Ziden et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, four qualitative studies were included (Ramli et al, 2022;Sarnat et al, 2019;Gökhan Sontay & Karamustafaoglu, 2021;Wommer et al, 2021), along with two quantitative control randomized (Dehghani, Mohammadhasani, Hoseinzade Ghalevandi, & Azimi, 2023;Maraza-Quispe et al, 2023) and one study employing a quantitative descriptive research design (Mustami et al, 2019). Furthermore, the selected articles were published in various journals, with two articles each in the following journals: International Journal of Information and Education Technology (Maraza-Quispe et al, 2023;Nurhayati et al, 2022), Journal of Science, Environment and Health Education (Omurtak & Zeybek, 2022;Serdar Yıldırım, 2021), Malaysian Journal of Online Education Technology (Gokhan Sontay & Karamustafaoğlu, 2021;Yapici & Karakoyun, 2021), TEM Journal (Damopolii et al, 2022;Lam et al, 2023), and one article each in Advances in Physiology Education (Gregorcic & Torkar, 2022), Eurasia Journal of Mathematics, Science and Technology Education (Ziden et al, 2022), European Journal of Contemporary Education (Fuchsova & Korenova, 2019), Interactive Learning Environments (Dehghani et al, 2023)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, several researchers are also interested in using mix-methods (4 articles). Another interesting thing is the augmented reality trend which is approached by R&D. -Muqbil, 2022;Cahyana et al, 2023;Cejka et al, 2021;Chuang et al, 2023;Kumar et al, 2023;López-Cortés et al, 2021;Petrov & Atanasova, 2020;Wang et al, 2022) 2 Qualitative 21 (Abriata, 2020;Aivelo & Uitto, 2016;Annisa & Subiantoro, 2022;Borrel & Fourches, 2017;Bouksim et al, 2018;Bursjöö, 2022;Celik et al, 2020;Cortés Rodríguez et al, 2022;Fuchsova & Korenova, 2019;Gregorcic & Torkar, 2022;Lam et al, 2023;Loucif et al, 2019;Maraza-Quispe et al, 2023;Nasharuddin et al, 2021;Nuanmeesri, 2018;Pence, 2020;Reeves et al, 2021;Rodríguez et al, 2021;Saidin et al, 2015;Stojšić et al, 2022).…”
Section: Research Types/methodsmentioning
confidence: 99%